Optimization of pharmacological interventions in the guinea pig animal model—a new approach to calculate the perilymph volume of the scala tympani - Grzybowski, Marleen; Malfeld, Kathrin; Lenarz, Thomas; Scheper, Verena; Schurzig, Daniel (Frontiers in Neuroscience, 2023)
therapeutic interventions of the auditory system. However, the heterogeneity of results observed in both in-vivo experiments and clinical studies poses challenges in understanding and optimizing pharmacotherapy outcomes. This heterogeneity may be due to individual differences in the size of the guinea pig cochlea and thus in the volume of the scala tympani (ST), which can lead to different drug concentrations in the ST, a fact that has been largely overlooked thus far. To address this issue, we aimed to develop an approach for calculating the individual volume of perilymph within the ST before and after cochlear implant insertion. Method: In this study, high-resolution µCT images of a total of n=42 guinea pig temporal bones were used to determine the volume of the ST. We compared fresh, frozen, and fixed tissues from both coloured and albino strains to evaluate the potential influence of tissue condition and strain on the results. Results: Our findings demonstrate a variability in mean ST volume with a relative standard deviation (RSD) of 14.7%, comparable to studies conducted with humans (range RSD: 5% to 20%). This indicates that the guinea pig cochlea exhibits similar variability to that of the human cochlea. Consequently, it is crucial to consider this variability when designing and conducting studies utilizing the guinea pig as an animal model. Furthermore, we successfully developed a tool capable of estimating ST volume without the need for manual segmentation, employing two geometric parameters, basal diameter (A) and width (B) of the cochlea, corresponding to the cochlear footprint. The tool is available for free download and use on our website. Conclusion: This novel approach provides researchers with a valuable tool to calculate individual ST volume in guinea pigs, enabling more precise dosing strategies and optimization of drug concentrations for pharmacotherapy studies. Moreover, our study underscores the importance of acknowledging and accounting for inter-individual variability in animal models to enhance the translational relevance and applicability of research outcomes in the field of inner ear investigations.